ASSA13-06-4 Female Sex Predicts Poor Prognosis in Patients with Hypertrophic Cardiomyopathy. (29th April 2013) - Yilu, Wang; Jingru, Bao; Kai, Sun; Ling, Zhu; Tao, Tian; Hu, Shen; Weili, Zhang; Yubao, Zou; Jizheng, Wang; Xianliang, Zhou; Ferhaan, Ahmad; Rutai, Hui; et al.
Abstract : Objective: This study was designed to assess the sex effect on clinical presentation and outcomes in patients with hypertrophic cardiomyopathy (HCM). Sex has been proved to play an important role in the clinical expression and prognosis of various cardiovascular diseases. Methods: A total of 621 unrelated patients with HCM, without heart failure (460 males) were enrolled from 1999 to 2011. Results: At baseline, female patients were older (49.6 ± 17.2 years vs. 46.7 ± 14.4 years, p = 0.033) at diagnosis, had greater frequency of left ventricular outflow tract obstruction (72/161, 44.7% vs. 149/460, 32.4%, p = 0.005) than male patients. During follow-up of 4 (2–7) years, survival analysis showed that the incidences of all-cause mortality, cardiovascular death and progression to chronic heart failure were greater in women than in men ( p = 0.031, 0.040 and 0.014, respectively). After adjustment for multiple factors that may confound survival and cardiac function, female sex remained an independent risk factor for all-cause mortality, cardiovascular death, and chronic heart failure [hazard ratio (HR) 2.19, 95% confidence interval (CI) 1.21–3.95, p = 0.010; HR 2.19, 95%CI 1.17–4.09, p = 0.014; HR 1.73, 95%CI 1.12–2.69, p = 0.014, respectively] in HCM patients. Subgroup analysis revealed that female sex as a risk factor was only identified in patients younger than 50 years old ( p = 0.011, 0.011 and 0.020, respectively), but not in more than 50 years old. Conclusions: Our results suggest that female sex is an independent predictor of poor survival and heart failure in HCM patients. Further studies were required to determine whether female hormones modify the clinical expression and prognosis of HCM.